Clinical Profile of Diabetic Foot Amputation in Hasan Sadikin Hospital, Bandung, Indonesia - Andhika, Cakra (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Diabetes mellitus related to foot ulcers is common. Most studies use amputation rates as a measure of foot management in diabetics. The aim of this study was to determine the description of diabetic foot clinical profile at Hasan Sadikin Hospital, Bandung, Indonesia. The study was conducted on diabetic foot who came to Hasan Sadikin Hospital, Bandung from January 2014 to December 2018, retrospectively. There are 243 diabetic foot patients at Hasan Sadikin Hospital in this study. There are 112 males (46.1%) and 131 females (53.9%). There are more patients with the duration of diabetes was more than 10 years than the shorter duration of diabetes. The 51-60 year age group is the group with the largest percentage (41.6%). Based on the Wagner classification group, patients with grade 2 Wagner diabetic foot became the most group (28.4%). Total amputations were 91 patients (37.5%). The most diabetic foot management is debridement, which is 110 patients (45.3%). The most common type of amputation is below knee amputation, which is 45 patients (49.5%).